K. H. Ahmad Dahlan: Konsep dan Implementasi “Kemanusiaan” (1912-1936) - Wasno Wasno; Rhoma Dwi Aria Yuliantri (Department of History, Faculty of Humanities, Diponegoro University, 2022)
Ahmad Dahlan is an Islamic reformer known for one of his concepts of humanity (compassion). This research aims to examine Ahmad Dahlan's thoughts and practices about the humanitarian concept of